IMPLEMENTASI MODEL CONNECTING, ORGANIZING, REFLECTING, EXTENDING TERHADAP KEMAMPUAN PENALARAN MATEMATIS MATERI TEOREMA PYTHAGORAS KELAS VIII - Isna Musri'ah; Abdul Aziz; Dwi Sulistyaningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Merdeka Curriculum aims to shape students to be faithful, virtuous, creative, and possess character aligned with Pancasila values. Mathematics, as a fundamental subject, plays an important role in training logical, critical, and creative thinking skills. One of the key topics taught in eighth grade is the Pythagorean Theorem, which has many real-life applications and requires strong mathematical reasoning skills. Observations at SMP Negeri 1 Siwalan revealed that students’ mathematical reasoning abilities remain low, with an average daily score of only 50%. This condition is influenced by the use of conventional learning methods, lack of active participation, and low student motivation. Therefore, an innovative learning model is needed, such as CORE (Connecting, Organizing, Reflecting, Extending). This study aims to determine the differences in mathematical reasoning ability between students taught using the CORE model and those taught through conventional methods, to describe students’ responses toward the CORE model, and to examine its influence on learning outcomes. The research employed a quasi-experimental method with a Posttest-Only Design with Nonequivalent Groups, involving two eighth-grade classes at SMP Negeri 1 Siwalan, each consisting of 32 students. Research instruments included essay tests and non-test methods (observation and interviews), with prior validity and reliability testing. Data analysis was conducted using SPSS version 25. The results showed a significant improvement in the experimental class compared to the control class. Moreover, students responded very positively to the CORE model, as it enhanced motivation, activeness, and provided more meaningful learning experiences in the Pythagorean Theorem topic.